Art et réforme clunisienne : le porche sculpté de Beaulieu-sur-Dordogne - Barbara Franzé (Bulletin du Centre d’Études Médiévales d’Auxerre)
The sculpted porch of the abbaye of Beaulieu-sur-Dordogne, dated 1130’-1140’ by recent studies, presents a rich iconographic programme which was, until today, only partially analysed. The cross-approach of various indications, which associates written documents and stylistic comparisons, indicates a realisation in the first years of the 12th century, namely in the time of abbot Géraud (1095-v. 1199). Of cluniac origin, Géraud managed, after the failure of his predecessors, to reform his abbey which enjoyed of a prosperity nevermore reached in the future.For the conception of the iconographic programm of the south porch which was intended to the laic community, the abbot seems to have drawned in the vaste literary corpus of Grégorius Magnus, corpus particularly estimated by reformers and clunisians, during the 11th and 12th centuries.